Experimental Study on Sansivera Composite Fibers Against the Administration of Alkaline NaOH (Sodium Hydroxide): Studi Eksperimental pada Serat Komposit Sansivera Terhadap Alkali NaOH (Natrium Hidroksida) - Kurniawan, Teguh Tri; Widodo, Edi (Procedia of Engineering and Life Science, 2023)
This study aims to analyze sansivera fiber-reinforced composite materials with a polyester resin matrix and treat sansivera fibers against alkaline NaOH liquids with levels of 4%,7%,10%,13% and 15%.in this study for experimental design using the hand lay-up method,which aims to analyze experimental data,and is also used to determine the minimum number of experiments that can be obtained and provide infotmation on factors that influence parameters.The experiments were carried out through 1)composite manufacturing method,2)immersion with alkaline NaOH,3)fiber tensile test method,4)microstructure test method,5)composite tensile test methods.the results of research on tensile test of fibers from the soaking process with alkaline NaOH 4%,7%,10%,13% and 15%,get the best results in the 15% NaOH alkaline immersion process. From results of the tensile test the fibers will be formed into 7 composite specimens, from the composite tensile test the maximum tensile strength is obtained on specimen 5 with 40% treatment of 45,71 N/mm2 and the highest elongation obtained on specimen 4 with 30% treatment of 3,95mm.